Síntese de sistemas estritamente reais positivos através do critério de routh-hurwitz - Covacic, Márcio Roberto; Assunção, Edvaldo [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Cardim, Rodrigo [UNESP] (FapUNIFESP (SciELO), 2010)
Given a linear time-invariant plant Gol(s) with one input and q outputs, where q > 1, a method based on the Routh-Hurwitz Stability Criterion is proposed to obtain a constant tandem matrix F ∈ ℝq, such that FGOl(s) is a minimumphase system. From this solution, the system FGol(s) is represented in state space by {A, B, FC} and a constant output feedback matrix K0 ∈ ℝ is obtained such that the feedback system {A - BK0C, B, FC} is Strictly Positive Real (SPR). The proposed procedure offers necessary and sufficient conditions for both problems. Initially, the general case, with a generic q, is analyzed. Following, the particular cases q = 2 and q = 3 are studied.
SPR systems synthesis through routh-hurwitz criterion
Keywords: Minimum phase; Output feedback; Routh-hurwitz criterion; SPR systems; Feedback systems; Linear time invariant plant; matrix; Minimum-phase systems; Routh-Hurwitz; Routh-Hurwitz criterion; State space; Strictly positive real; Sufficient conditions; Feedback control; Stability criteria; State feedback; Feedback